No princípio era o erro: algumas reflexões sobre a mudança linguística - Barros, Clara (CEM – Cultura, Espaço & Memória, 2019)
This article discusses the way in which the speakers and the linguistic community face the phenomena of linguistic change. From an empirical and normative perspective, the traditional way of speaking is considered correct and the new forms are considered errors, a deviation from what is considered good linguistic use. However, this definition of «error» in language is also associated with parameters of social, cultural and geographical variation. The paper also briefly mentions how linguistic change has been analysed in the context of several currents of linguistics. Finally, some cases of innovation in current Portuguese are examined, innovations which are manifested in pronunciation, but also in new grammatical and lexical uses. Finally, it is considered that an error as a deviation from a previous, traditional norm is an unmistakable sign of linguistic change.